Utilization of poultry waste as feed and supplementary feed for fish growth - S.O. Usman; K.U. Ogbe; J.U. Oguche; T.B. Momoh; S Omale (Journal of Applied Sciences and Environmental Management, 2019)
This research work was carried out to evaluate poultry waste as a potential feed for fish growth. The poultry droppings were collected for analysis. The parameter determined to ascertain the potential of this poultry waste were proximate analysis (Moisture, dry matter, ash, crude protein, fat, crude fibre and carbohydrate contents) and mineral nutrient composition (calcium, potassium, magnesium, sodium, copper, zinc, iron and manganese). The proximate analysis determined estimated moisture content to be 9.62±0.02%, dry matter 90.38±0.03%, ash content: 28.83±0.29%, crude protein: 21.34±0.16%, fat content: 2.61±0.13%, crude fibre:16.09±0.04, and carbohydrate: 21.53±0.03. The minerals nutrient composition for metals analysed is as follows; calcium: 2349.9±56.57mg/kg, potassium: 6239±572.76mg/kg. Magnesium: 1075.0±141.42mg/kg, sodium: 292.3±10.61mg/kg, copper: 104.8±7.07mg/kg, zinc: 395.0±7.07mg/kg, iron: 519.7±7.07mg/kg and manganese: 257.5±10.61mg/kg. However, based on the result for proximate analysis of the poultry waste analysed and mineral nutrients estimated compared with the mineral nutrient requirement of fish the results were not adequate for direct use as feed for fish. Thus the poultry droppings could only serve as feed or supplement for the conventional fish feeds use for fish to give excellent growth rate.